The Relationship between the Ummi Model and the Ability to Read the Qur'an of Third Grade Students at School - Fujiati Fujiati; Moch. Bahak Udin By Arifin (Indonesian Journal of Islamic Studies, 2021)
The purpose of this study was to determine the relationship between the Ummi Model and the ability to read the Qur'an of third graders at the SDIT Nurul Islam Krembung school. This study uses quantitative research using data collection instruments, in this study using primary and secondary data sources to determine the subjects from which the data was obtained, and using questionnaire data collection procedures with question and answer interviews to take notes on events. The sample used in this study were all 3rd grade students of SDIT Nurul Islam Krembung, amounting to 25 of which 13 or 52% of students scored well, 9 students or 36% had sufficient marks, 3 students or 12% with poor grades, this means reading ability in the good category is in the good category. in a score of 83-91. It can be concluded that the relationship between the ummi model has an effect on the ability to read the Qur'an of third graders at SDIT Nurul Islam Krembung.